Can nonalcoholic beer, silicon and hops reduce the brain damage and behavioral changes induced by aluminum nitrate in young male Wistar rats?. (August 2018) - Merino, P.; Santos-López, J.A.; Mateos, C.J.; Meseguer, I.; Garcimartín, A.; Bastida, S.; Sánchez-Muniz, F.J.; Benedí, J.; González-Muñoz, M.J.
Abstract: Aluminum consumption has been associated with various neurodegenerative diseases. Previous studies suggest that regular beer intake reverses the pro-oxidant and inflammatory statuses induced by aluminum nitrate intoxication. This paper aims to evaluate the in vitro antioxidant capacity and acetylcholinesterase inhibitory activity of non-alcoholic beer (NABeer), silicon or hops, as well as their effect on animal behavior (e.g. curiosity, immobilization, rearing, grooming, swimming) and brain antioxidant enzyme (activity and gene expression) and anti-inflammatory status in aluminum nitrate intoxicated rats. Male Wistar rats were divided into five groups: 1) Control, 2) Aluminum nitrate (450 μg/kg/day), 3) Aluminum nitrate plus NABeer, 4) Aluminum nitrate plus hops, and 5) Aluminum nitrate plus silicon. Hops showed the highest in vitro antioxidant capacity and silicon the highest anticholinesterase activity. In the Aluminum group the brain aluminum/silicon ratio increased with impairment of brain antioxidant and inflammatory statuses. NABeer, silicon and hops block the negative effect on the in vivo antioxidant and inflammatory statuses induced by Aluminum nitrate and improve swimming and rearing behavioral tests. The various positive results suggest that NABeer is useful as a functional multi-target drink in the prevention of some neurodegenerative events caused by aluminum intoxication. More studies are required to conclude present results. Graphical abstract: Highlights: Hops, Si and non-alcoholic beer show antioxidant and antiacetylcholinesterase activities. Chronic Al(NO3 )3 administration induces brain inflammation and oxidation in male rats. Animal behavior impairment was observed in Al(NO3 )3 intoxicated male rats. Hops, Si and non-alcoholic beer arrest the negative effect of aluminum intoxication.